PARS PLANA VITRECTOMY WITH ANTERIOR CHAMBER VERSUS GORE-TEX SUTURED POSTERIOR CHAMBER INTRAOCULAR LENS PLACEMENT: Long-Term Outcomes. Issue 5 (May 2019) - Khan, M. Ali; Gupta, Omesh P.; Pendi, Kasim; Chiang, Allen; Vander, James; Regillo, Carl D.; Hsu, Jason
Abstract : Purpose: To compare clinical outcomes of combined pars plana vitrectomy (PPV) with anterior chamber intraocular lens (ACIOL) placement versus scleral fixation of a posterior chamber intraocular lens (PCIOL) using Gore-Tex suture. Methods: Retrospective, interventional case series of eyes undergoing combined PPV and IOL placement for retained lens material, aphakia, or dislocated IOL. Eyes with history of amblyopia, corneal opacity, retinal, or optic nerve disease were excluded. Outcome measures were change in visual acuity and occurrence of postoperative complications with minimum follow-up of 1 year. Results: Sixty-three eyes of 60 patients were identified. Thirty-three eyes underwent combined PPV and ACIOL placement and 30 eyes underwent combined PPV and scleral fixation of a PCIOL using Gore-Tex suture. Mean follow-up was 502 ± 165 days (median 450, range 365–1, 095 days). In the ACIOL group, mean visual acuity improved from 20/914 preoperatively to 20/50 postoperatively ( P < 0.001). In the scleral-fixated PCIOL group, mean visual acuity improved from 20/677 preoperatively to 20/46 postoperatively ( P < 0.001). No difference in visual acuity was noted between groups at 1-year ( P = 0.91) or final follow-up ( P = 0.62). Regarding postoperative complications, eyes undergoing ACIOL placement had a significantly higher rate of transient corneal edema (30.3 vs. 6.7%, P = 0.02) compared with eyes undergoing scleral fixation of a PCIOL. Conclusion: Combined PPV with ACIOL placement or scleral fixation of a PCIOL with Gore-Tex suture were well tolerated. The techniques resulted in similar visual outcomes at minimum follow-up of 1 year. Abstract : Comparative analysis of combined vitrectomy with anterior chamber intraocular lens placement versus scleral fixation of a posterior chamber intraocular lens using Gore-Tex suture revealed similar visual acuity outcomes at minimum follow-up of 1 year. Regarding postoperative complications, transient corneal edema was more common with use of an anterior chamber intraocular lens.